1971
DOI: 10.1042/bj1210683
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis by membrane-bound and free ribosomes of secretory and non-secretory tissues

Abstract: 1. Methods for the separation of membrane-bound and free ribosomes from rat brain (cortex) and skeletal muscle were described and the preparations characterized by chemical analysis and electron microscopy. The attachment of ribosomes to membranes is not an artifact of the separation procedure. 2. The rate of incorporation of l-[(14)C]leucine into protein in vitro by the membrane-bound and free ribosomes from these two predominantly non-protein-secreting tissues is compared with that by similar preparations fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
1

Year Published

1973
1973
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(42 citation statements)
references
References 49 publications
4
37
1
Order By: Relevance
“…The relative distribution of the two ribosome classes greatly depends on the cell type. Thus, cells active in the synthesis of secretory proteins contain a large proportion of bound ribosomes (3,4), whereas cells synthesizing proteins primarily for intracellular use have most of their ribosomes in the free state (5,6). In a limited number of cases, it has been shown that the free and membrane-bound ribosomes are indeed involved in the synthesis of different classes of proteins (3,(7)(8)(9)(10)(11), in agreement with the generalization mentioned above.…”
supporting
confidence: 68%
“…The relative distribution of the two ribosome classes greatly depends on the cell type. Thus, cells active in the synthesis of secretory proteins contain a large proportion of bound ribosomes (3,4), whereas cells synthesizing proteins primarily for intracellular use have most of their ribosomes in the free state (5,6). In a limited number of cases, it has been shown that the free and membrane-bound ribosomes are indeed involved in the synthesis of different classes of proteins (3,(7)(8)(9)(10)(11), in agreement with the generalization mentioned above.…”
supporting
confidence: 68%
“…The intense OP-puro labeling of vesicles in Paneth cells (Fig. 3A, Bottom) suggests that prematurely terminated, OP-puro-conjugated secretory proteins are translocated into the endoplasmic reticulum (ER) lumen, as described before for puro (28). The same pattern of OP-puro labeling was observed in whole-mount stains of the small intestine (Fig.…”
supporting
confidence: 56%
“…In lysates from neuroblastoma cells, the incorporation of [3Hileucine into proteins was linear during 20 min and reached a plateau after 30 min of incubation (Fig. 1B).…”
Section: Methodsmentioning
confidence: 99%
“…The specific activity of native ribosomes (free and membrane-bound) was about twice higher in monolayer than in suspension cells (Table 3). Since it has been reported (14,20) that, in in vitro systems, membrane-bound ribosomes are more active than free ribosomes during short incubation times, the difference in activity of native ribosomes could be due to a change in the relative amounts of free and membranebound ribosomes in the two cell populations. Therefore, neuroblastoma ribosomes were treated with 1% deoxycholate (final concentration), so that all ribosomes would be present as free particles.…”
Section: Cell Sap Activitymentioning
confidence: 99%